Composition of the Cortes as a result of the first ballot
014_0033_001 August Composition of the Cortes as a result of the first ballot:- Left Coalition: Socialists 85 Izquierda Republicana 75 Union Republica 32 Esquerra 20 Communists 14 Other Left groups 30 256. Right Parties: C.E.D.A. 94 Agrarians 12 Monarchists 12 Independents 11 Traditionalists 11 Others 3 143. Centre Parties: Portelists 19 Lliga 11 Radicals 8 Progressists 6 Others 11 55 The Second Ballot was for 20 seats. According to the "Times" the result should give eight more Deputies to the Left Coalition, five to the Right Coalition, two to the Centre and five to the Basque nationalists. "Times" 27.2.36. and 3.3.36. 292/946/14/33